Code of Ethics for Teachers in Islamic Education Perspective Muhammad Athiyah Al-Abrasyi - Masrizal; Marzuki; Syahrul Awali; Azmi Yudha; Maria Ulfa; Nurul Aida (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Education can be simply interpreted as an effort to shape human personality in accordance with the values ​​and codes of ethics contained in society and the country. One of the most important components in the learning process is educators and students. Along with the times, there is a shift in the pattern of teacher and student relations; economic values ​​have driven many policies, the appreciation of students towards teachers has decreased, the price of teacher's work is higher, and the teacher's appreciation for him has been lower. Considering the urgency of the teacher's role in the education process, many scholars wrote about the obligations, traits or tasks that the teacher and students had to have. Based on this background, the writer formulates the problem of the teacher's code of ethics in the perspective of Islamic education, Muhammad Athiyah Al-abrasyi. This research is a qualitative descriptive study with the type of library research. The results of this study include personal and professional aspects. The code of ethics of teachers in Islamic education proposed by Muhammad Athiyah al-Abrasyi includes: 1. The code of ethics of teachers relating to themselves; a. Be zuhud, b. Clean from sin and reprehensible qualities. 2. The teacher's code of ethics relating to students and fellow teachers; a. Be wise and firm, b. Forgiving and patient, c. Having dignity and self-esteem, d. Loving students is like loving their own children, e. Knowing students' habits. 3. Code of ethics for teachers related to their duties; a. Sincere at work, b. Mastering the field of study, c. Be able to create active communication between educators and students.